Personal and social wellbeing of teenagers and prevention of disconfor and violence : presentation and validation of an educational program - Carpintero, Eugenio (2007)
We present a programme aimed at helping adolescents to feel more at ease with themselves and with others, to better face the difficulties of life and to engage in fewer risk behaviours.